Characteristics of Palliative Patients, Insights of Patients and Families, and the Impact of Estimated Survival Time on Therapy Decisions - Hamzah Shatri; Rudi Putranto; Cosphiadi Irawan; Mizanul Adli; Dina Elita (Acta Medica Indonesiana, 2019)
Background: chronic and terminal diseases require holistic therapy that covers the biopsychosocial aspect, and it can be found in palliative therapy. Patients who receive palliative therapy exhibit very diverse profiles. As such, researchers are keen to study the general characteristics of palliative patients. In addition, researchers will also assess the patient’s and their family’s insight that influences the success of the therapy and the impact of estimated survival time in making treatment decisions. Methods: this research used cross-sectional descriptive analytic study and secondary data of 300 palliative patients who consult to Psychosomatic Palliative Team at Dr. Cipto Mangunkusumo Hospital. The data were processed using SPSS version 25. The data processed included: sociodemographic characteristics, length of stay, incidence of death in hospital, DNR cases, the patient’s and their family’s insight, and the impact of estimated survival time on treatment decisions. Results: most palliative patients were women (52.0%) aged 51 - 60 years (27.0%), unemployed (29.0%), and suffered from cancer (55.3%). In addition, the patients were generally treated for less than 1 month (83.6%), died in the hospital (37.3%), and consented to DNR orders (36.7%). These DNR cases are highly correlated to the family’s understanding regarding the prognosis of the patient’s condition (p = 0.022). The family’s understanding of the diagnosis, prognosis, and treatment goals (92.3%, 81.3%, and 87.7%) was better than the patient’s (79.0%, 64.0%, and 69.7%). Furthermore, no link was found between the therapy choice (optimal, withholding, and withdrawing therapies) with the patient’s estimated survival time (p = 0.174). Conclusion: female, elderly, and cancer patients most often get palliative therapy. The consent for DNR orders to palliative patient is notably frequent. Currently, the family’s insight is much better than the patient’s, which means that health care providers need to improve patient education and information. In addition, patients and families generally still opt for optimal therapy despite low estimated survival time.